Kontekstualisasi Nilai-Nilai Aswaja dalam Berbagai Sendi Kehidupan, 2021, ISBN 9786239726522 - Syukron Ma’mun (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2023)
The title of the book "Kontekstualisasi Nilai-Nilai Aswaja dalam Berbagai Sendi Kehidupan" translates to "Contextualization of Aswaja Values in Various Aspects of Life." This is a book written by Dr. H. A. Zaki Mubarak and his colleagues. This book is a significant work in explaining fundamental concepts in Islam, particularly Ahlussunnah Wal Jama'ah (Aswaja), and how these values can be applied in various aspects of daily life. In this book, the authors aim to strengthen the understanding of Aswaja and build awareness of the importance of applying these values in everyday life. The book is well-designed and based on solid research, providing readers with a clear understanding of the concepts and teachings of Aswaja. The authors clearly describe the history and important principles that form the basis of these values. They elaborate on the concepts of monotheism (tauhid), faith (akidah), and worship practices, as well as providing in-depth insight into the concept of life in accordance with Aswaja teachings